PENGADAAN OBAT DI GUDANG FARMASI RUMAH SAKIT RAJAWALI CITRA BANTUL - Dendo, Angelina; Subandi, Subandi (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2026)
This study aims to obtain information on drug procurement in pharmacy warehouses, including the purchase method of